New distribution records for Phalangopsinae, Indozacla Gorochov, 2018, and Meloimorpha cincticornis Walker, 1870 in China, along with a report on a new species Indozacla dorsiglaber Ma & Wang sp. nov. (Orthoptera: Phalangopsidae) - Wang, Ning; Xie, Can-Hong; Zhang, Tao; Ma, Li-Bin (Zootaxa, 2025)
This study documents significant distributional expansions of three orthopteran taxa in China and describes a new species from the Tibetan Plateau. We present the first confirmed records of the subfamily Phalangopsinae, genus Indozacla Gorochov 2018, and species Meloimorpha cincticornis Walker 1870 in China. This newly discovered Indozacla dorsiglaber Ma & Wang sp. nov. exhibits wing sexual dimorphism, with males having short wings and females wingless. Comprehensive morphological descriptions, diagnostic comparisons, and ecological photographs are provided, supplemented by COX1 molecular data exploring the systematic relationships of several species. These findings extend the known northern limits of Phalangopsinae in Asia and contribute to understanding Himalayan orthopteran diversity.